2022
DOI: 10.1101/2022.02.15.22270564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heated tobacco products and a telemedicine smoking cessation programme: A retrospective study

Abstract: Objectives: Japan is one of the largest markets for heated tobacco products (HTP), and the number of HTP users, including dual users, is burgeoning. However, it is not yet clear whether a telemedicine smoking cessation programme is helpful for nicotine-dependent people who use HTPs. Methods: We retrospectively evaluated the effectiveness of a telemedicine smoking cessation programme for nicotine-dependent tobacco product users, comparing short- and long-term continuous abstinence rates (CAR) from 9 to 24 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Nomura et al previously reported the efficacy of a telemedicine smoking cessation program for nicotine-dependent people who used HTPs over an 8-week telemedicine program provided by primary physicians and a 10-month follow-up period (sending surveys and smoking cessation advice via the app). 22 They found that exclusive HTP users had significantly higher CAR 9–24 than the exclusive cigarettes group (53·8% for cigarettes vs. 67·0% for HTP). These reports are consistent with the present results, and they suggest the efficacy of the online smoking cessation treatment for exclusive HTP users.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nomura et al previously reported the efficacy of a telemedicine smoking cessation program for nicotine-dependent people who used HTPs over an 8-week telemedicine program provided by primary physicians and a 10-month follow-up period (sending surveys and smoking cessation advice via the app). 22 They found that exclusive HTP users had significantly higher CAR 9–24 than the exclusive cigarettes group (53·8% for cigarettes vs. 67·0% for HTP). These reports are consistent with the present results, and they suggest the efficacy of the online smoking cessation treatment for exclusive HTP users.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have reported lower smoking cessation rates for dual users as compared to their counerparts. 22 Another report showed no difference in smoking cessation behavior between dual users and cigarette users. 24 Thus, the present results might be the consequence of the offsetting advantages and disadvantages among dual users.…”
Section: Discussionmentioning
confidence: 98%